PERSEPSI MAHASISWA TERHADAP PENANGANAN COVID-19 DI KABUPATEN OGAN KOMERING ULU - Mega Lisa; Tiara Priscalia; Leoen Leoen; Hagay Krisnanda Maranata; Herwin Sagita Bela (JURNAL DINAMIKA, 2022)
According to the WHO website, coronaviruses are a large family of viruses that can cause disease in animals or humans. In humans, corona is known to cause respiratory infections ranging from the common cold to more severe diseases such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). Covid-19 is a disease caused by infection with the SARS-CoV-2 virus, first identified in the city of Wuhan, in China's Hubei province in December 2019. Several policies set by the central government such as closing schools, campuses, closing several private companies, closing entertainment centers, closing several tourist attractions, implementing PSBB, in addition, during this pandemic the government also provided some social assistance such as in the form of basic necessities and cash. , while in local governments such as in OKU district, the government has provided several policies such as closing schools and campuses, providing facilities to limit operations in eating places such as restaurants and cafes, giving an appeal to apply 5M to prevent the spread of the corona virus. seen from the respondents' answers that students' perceptions of the handling of Covid-19 in the district. This OKU has indeed been good, seen from the preparation of places for quarantine, giving advice to restaurant, café or mall owners to close early, giving warnings through banners to maintain health and implementing 5M, the government has also provided services for vaccinations in order to overcome the spread of covid.